Effect of Intra Group Transaction, Thin Capitalization and Executive Characters on Tax Avoidation with Multinationality as a Moderation - Bandiyono, Agus; Murwaningsari, Etty (Journal of Accounting, Business and Finance Research, 2019)
The purpose of this study is to examine the factors of tax avoidance in business groups / corporate groups in Indonesia, especially those belonging to the property sector which is listed on the Indonesia Stock Exchange (IDX) using variables such as intragroup transaction, thin capitalization, executive character and multinationality and firm size, profitability, intangible assets and debts as control variables. In this research, the object taken is secondary data, namely the financial statements of business groups / corporate groups included in the property sector group in 2012-2016. The data obtained from the IDX. Therefore, the author decided to choose the last 5 years period, 2012 until 2016. The data used in this study was in the form of balanced panel data, where the data of each unit object (cross section) will be observed in the same time period. The results showed that variables of intra group transaction and executive character had positive and significant effect on tax avoidance, while thin capitalization proved to have no effect on tax avoidance. While the multinationality variable managed to moderate the influence of intra group transaction, executive character and thin capitalization on tax avoidance.